Mechanism of GTP hydrolysis by G-protein alpha subunits. - Kleuss, C (1994)
Hydrolysis of GTP by a variety of guanine nucleotide-binding proteins is a crucial step for regulation of these biological switches. Mutations that impair the GTPase activity of certain heterotrimeric signal-transducing G proteins or of p21ras cause tumors in man. A conserved glutamic residue in the alpha subunit of G proteins has been hypothesized to serve as a general base, thereby activating a water molecule for nucleophilic attack on GTP. The results of mutagenesis of this residue (Glu-207) in Gi alpha 1 refute this hypothesis. Based on the structure of the complex of Gi alpha 1 with GDP, Mg2+, and AlF-4, which appears to resemble the transition state for GTP hydrolysis, we believe that Gln-204 of Gi alpha 1, rather than Glu-207, supports catalysis of GTP hydrolysis by stabilization of the transition state.